The Solar Water Pump For Agriculture Irrigation For Community Village In Jono Temayang Bojonegoro - Maghfiroh, Amalia Ma'rifatul; Anisa, Zuffa; Mushthofa, Mushthofa (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Increasing agricultural productivity is highly dependent on the need for water for irrigation. Water is a vital component for human, animal, and plant life. Therefore, farmers need knowledge and innovation in water management. In Jono Temayang Village, Bojonegoro, the problem of drought is very much felt, especially during the dry season, because irrigation still depends on rain-fed wells. The Luhur Farmers Group in Jono Village grows rice, tobacco, and corn, but has difficulty in providing sufficient irrigation water. Although there are irrigation channels, higher rice fields often lack water. Farmers use portable pumps that require fuel, but in conditions of water shortages, they are forced to draw water manually. The purpose of this activity is to provide socialization and training on the use of PLTS-based water pumps to facilitate irrigation and reduce fuel use. The training socialization is divided into 3 materials, namely material on irrigation management, introduction and assembly of PLTS and finally maintenance of PLTS-based water pumps.